Prototype of high accuracy single input phase measurement instrument. (30th September 2022) - Tudosa, Ioan; Picariello, Francesco; Daponte, Pasquale; De Vito, Luca; Rapuano, Sergio; Paulter, Nicholas G.
Highlights: Single input sine-wave signal phase measurement; No need for isofrequential reference; Prototype working frequency range of 100 Hz to 10 MHz; Maximum experimental standard deviation of 0.021° at 10 MHz. Abstract: A prototype implementation of a phase measurement method (PMM) for a sine-wave signal delivered at the output port of a generator and its experimental assessment is presented. This PMM is capable of measuring the output phase of a sine-wave signal respect to a reference phase with high accuracy and a very low uncertainty. A description of the prototype PMM, and its mathematical model are given in the paper. The prototype operates over the frequency range of 100 H z to 10 M H z and it is composed from three main subsystems: (i) the sampling circuit, (ii) the pulse-train signal generator, and (iii) the data acquisition and digital signal processing. A laboratory test bench was realized to assess the phase measurement repeatability of the prototype, and a maximum phase standard deviation of 0 . 021 ° measured at 25 ° C was obtained for the output frequency of 10 M H z, where the phase uncertainty decreases with decreasing frequency.